Patients' perspectives on interprofessional collaboration between health care professionals during hospitalization: a qualitative systematic review. Issue 6 (June 2020) - Didier, Amélia; Dzemaili, Shota; Perrenoud, Béatrice; Campbell, Joan; Gachoud, David; Serex, Magali; Staffoni-Donadini, Liliana; Franco, Loris; Benaroyo, Lazare; Maya, Zumstein-Shaha
ABSTRACT: Objective: The objective of this review was to gain a better understanding of the interprofessional collaboration between health care professionals from the patients' point of view during hospitalisation; the influence of interprofessional collaboration on patient care, safety, and well-being; and patients' perspectives of their role in the interprofessional collaboration process. Introduction: Interprofessional collaboration is a key factor in improving patient health care outcomes and safety through better communication between health care professionals, better teamwork, and better care coordination. However, implementing interprofessional collaboration in the clinical setting can prove complex. Patients are increasingly interested in becoming partners within the health care system. They have the potential to contribute to their own safety and to observe professionals during the care process, thus gaining a better understanding of the interprofessional collaboration process and facilitating changes in the behavior of health care professionals. Inclusion criteria: This review considered qualitative research and mixed-method studies. Participants were hospitalized patients. Studies were included when they explored i) patients' perceptions of interprofessional collaboration, ii) the influence of interprofessional collaboration on patients' care, safety, or well-being, or iii) patients' perceptions of their own role in interprofessional collaboration. Qualitative studies focusing only on the care process or families' points of view were excluded. Methods: Searches of six databases including MEDLINE, CINAHL, Embase, Web of Science, PsycINFO, and Sociological Abstract, limited to English, French, and German were conducted from March 2017 to June 2018. Assessment of methodological quality of studies was performed using the JBI Qualitative Assessment and Review Instrument. Data were extracted using the standardized data extraction tool from JBI. Data synthesis following the JBI approach of meta-aggregation was performed. The level of confidence for each synthesized finding was established based on ConQual. Results: A total of 22 studies were included, which resulted in 89 findings and 24 categories. Eight synthesized findings were generated: patients' perceptions of interprofessional collaboration based on personal experiences and observations; patients' experiences with effective or ineffective interprofessional communication; patients' experience with power imbalance and paternalistic attitudes; patients' perceptions of key factors for a confident relationship with the interprofessional health care team; patients' need for comprehension of discussions between health care professionals; patients' perceptions of their role in an interprofessional health care team; patients' perceptions of opportunities for empowerment in interprofessional health care teams; and patients' need for humanizing care from interprofessional health care teams. The level of confidence of synthesized findings varied from low to moderate according to ConQual. Conclusions: This systematic review synthesized the perspectives of hospitalized patients regarding interprofessional collaboration and their perceived role in collaborative practices. Hospitalized patients observe interprofessional collaboration, either directly or indirectly, and the way interprofessional collaboration is performed may impact both their care and their well-being. However, little evidence has been found regarding the impact of interprofessional collaboration on patient safety. Patients' perspectives on their perceived role is not unanimous; some patients want to play an active role in the collaborative process, whereas others prefer to trust the health care professionals' expertise. Health care professionals should consider patients' preferences and act accordingly regarding both the collaborative process and the inclusion of the patients in collaborative practices.